Live Imaging of Calciprotein Particle Clearance and Receptor Mediated Uptake: Role of Calciprotein Monomers - Koeppert, Sina; Ghallab, Ahmed; Peglow, Sarah; Winkler, Camilla Franziska; Graeber, Steffen; Büscher, Andrea; Hengstler, Jan Georg; Jahnen-Dechent, Willi (Frontiers in Cell and Developmental Biology, 2021)
Background: The liver-derived plasma protein fetuin A is a systemic inhibitor of ectopic calcification. Fetuin-A stabilizes calcium phosphate mineral initially as ion clusters to form calciprotein monomers, CPM, and then as larger multimeric consolidations containing amorphous calcium phosphate (primary CPP, CPP 1) or more crystalline phases (secondary CPP, CPP 2). CPM and CPP mediate excess mineral stabilization, transport and clearance from circulation. Methods: We injected i.v. synthetic fluorescent CPM and studied their clearance by live two-photon microscopy. We analyzed organ sections by fluorescence microscopy to assess CPM distribution. We studied cellular clearance and cytotoxicity by flow cytometry and live/dead staining, respectively, in cultured macrophages, liver sinusoidal endothelial cells (LSEC), and human proximal tubule epithelial HK-2 cells. Inflammasome activation was scored in macrophages. Fetuin A monomer and CPM charge were analyzed by ion exchange chromatography. Results: Live mice cleared CPP in the liver as published previously. In contrast, CPM were filtered by kidney glomeruli into the Bowman space and the proximal tubules, suggesting tubular excretion of CPM-bound calcium phosphate and reabsorption of fetuin A. Fetuin-A monomer clearance was negligible in liver and low in kidney. Anion exchange chromatography revealed that fetuin A monomer was negatively charged, whereas CPM appeared neutral, suggesting electrochemical selectivity of CPM versus fetuin A. CPM were non-toxic in any of the investigated cell types, whereas CPP 1 were cytotoxic. Unlike CPP, CPM also did not activate the inflammasome. Conclusions: Fetuin-A prevents calcium phosphate precipitation by forming CPM, which transform into CPP. Unlike CPP, CPM do not trigger inflammation. CPM are readily cleared in the kidneys, suggesting CPM as a physiological transporter of excess calcium and phosphate. Upon prolonged circulation, e.g. in chronic kidney disease, CPM will coalesce and form CPP, which cannot be cleared by the kidney, but will be endocytosed by liver sinusoidal endothelial cells and macrophages. Large amounts of CPP trigger inflammation. Chronic CPM and CPP clearance deficiency thus cause calcification by CPP deposition in blood vessels and soft tissues, as well as inflammation.